Mitochondrial DNA copy number and heteroplasmy load correlate with skeletal muscle oxidative capacity by P31 MR spectroscopy. Issue 11 (6th October 2021) - Tian, Qu; Moore, Ann Zenobia; Oppong, Richard; Ding, Jun; Zampino, Marta; Fishbein, Kenneth W.; Spencer, Richard G.; Ferrucci, Luigi
Abstract: The association between blood‐based estimates of mitochondrial DNA parameters, mitochondrial DNA copy number (mtDNA‐CN) and heteroplasmy load, with skeletal muscle bioenergetic capacity was evaluated in 230 participants of the Baltimore Longitudinal Study of Aging (mean age:74.7 years, 53% women). Participants in the study sample had concurrent data on muscle oxidative capacity (τPCr ) assessed by 31 P magnetic resonance spectroscopy, and mitochondrial DNA parameters estimated from whole‐genome sequencing data. In multivariable linear regression models, adjusted for age, sex, extent of phosphocreatine (PCr) depletion, autosomal sequencing coverage, white blood cell total, and differential count, as well as platelet count, mtDNA‐CN and heteroplasmy load were not significantly associated with τPCr (both p > 0.05). However, in models evaluating whether the association between mtDNA‐CN and τPCr varied by heteroplasmy load, there was a significant interaction between mtDNA‐CN and heteroplasmy load ( p = 0.037). In stratified analysis, higher mtDNA‐CN was significantly associated with lower τPCr among participants with high heteroplasmy load ( n = 84, β (SE) = −0.236 (0.115), p ‐value = 0.044), but not in those with low heteroplasmy load ( n = 146, β (SE) = 0.046 (0.119), p ‐value = 0.702). Taken together, mtDNA‐CN and heteroplasmy load provide information on muscle bioenergetics. Thus, mitochondrial DNA parameters may be considered proxy measures of mitochondrial function that can be used in large epidemiological studies, especially when comparing subgroups. Abstract : Mitochondrial DNA copy number and heteroplasmy load provide complementary information on mitochondrial oxidative capacity measured in skeletal muscle. The relationship between mitochondrial DNA copy number and muscle bioenergetics is different according to levels of heteroplasmy load. Assessing mitochondrial DNA copy number and heteroplasmy load may provide cost‐effective and accessible insight into muscle mitochondrial function in large epidemiological studies.